METTL3 knockout accelerates hepatocarcinogenesis via inhibiting endoplasmic reticulum stress response - Bo Cui; Silin Tu; Haibo Li; Zhancheng Zeng; Ruiqi Xiao; Jing Guo; Xiaoqi Liang; Chang Liu; Lijie Pan; Wenjie Chen; Mian Ge; Xiaofen Zhong; et al. (FEBS Open Bio)
Hepatocellular carcinoma (HCC) is among the most common causes of cancer‐related deaths worldwide. Previous studies showed that N6‐methyladenosine (m6A), the most abundant chemical modification in eukaryotic RNAs, is implicated in HCC progression. Using liver‐specific conditional knockout mice, we found that the loss of METTL3, the core catalytic subunit of m6A methyltransferase, significantly promoted hepatic tumor initiation under various oncogenic challenges, contrary to the previously reported oncogenic role of METTL3 in liver cancer cell lines or xenograft models. Mechanistically, we hypothesized that METTL3 deficiency accelerated HCC initiation by inhibiting m6A deposition on MANF transcripts, impairing nuclear export and thus MANF protein levels, which led to insufficient endoplasmic reticulum (ER) stress response pathway activation. Our findings suggest a tumor‐suppressive role for METTL3 in the early stages of HCC, emphasizing the importance of understanding the dynamic role of epigenetic regulation in tumorigenesis and targeted therapy.